INNOVATING WITHIN CONSTRAINTS: BASIC SCHOOL TEACHERS’ EXPERIENCES WITH PEDAGOGICAL REFORM IN GHANA - Benjamin Takyi; Samuel Korankye; Victoria Akolbila (International Journal of Teaching and Learning, 2026)
Ghana’s adoption of a standards-based curriculum grounded in 21st-century pedagogy presents a paradox: while teachers are trained in innovative, learner-centered methods, the classrooms they inhabit remain largely rigid, overcrowded, and under-resourced. This study investigates how basic school teachers navigate these tensions, implementing pedagogical innovations in traditional classroom environments. Using a parallel convergent mixed-methods design, the study engaged 97 basic school teachers through electronic surveys and in-depth interviews. Anchored in Rogers' Diffusion Innovation Theory, the study reveals that while pedagogical innovation is taking root at the cognitive and attitudinal levels, its full realization is obstructed by contextual constraints. The findings underscore the need for systemic reform beyond curriculum change, including infrastructure development and targeted teacher support. The study calls on educational policymakers to align pedagogical reforms with investments in physical learning environments to ensure sustainable and equitable educational transformation.